2013
DOI: 10.1186/1471-2334-13-315
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and clinical characteristics of multidrug and extensively drug-resistant tuberculosis in a tertiary care tuberculosis hospital in China

Abstract: BackgroundThere is a lack of information on the clinical characteristics of multidrug-resistant (MDR) tuberculosis (TB) and extensively drug-resistant (XDR) TB in the Jiangxi Province of China; furthermore, data have not been reported on the utility of mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) analyses in genotyping Mycobacterium tuberculosis strains isolated from this region. The aim of this study was to analyse the clinical features of patients with MDR and XDR TB f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
2
13
3
Order By: Relevance
“…In previous studies, researchers showed that IFITM3 played a critical role in the response of the immune system to influenza viruses, patients with the rs12252-C/C genotype of IFITM3 had more severe disease symptoms and worse clinical outcomes than the ones with T/T or T/C genotype (4,5,9). In the current study, both of the patients carried the T/C genotype, and their clinical outcomes were mild and 2…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In previous studies, researchers showed that IFITM3 played a critical role in the response of the immune system to influenza viruses, patients with the rs12252-C/C genotype of IFITM3 had more severe disease symptoms and worse clinical outcomes than the ones with T/T or T/C genotype (4,5,9). In the current study, both of the patients carried the T/C genotype, and their clinical outcomes were mild and 2…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies showed strong correlation between the IFITM3 and disease severity following influenza virus infection (4,5). For example, the presence of SNP IFITM3-rs12252 has direct correlation with the severity of the diseases associated with H7N9 infection (4).…”
Section: Case Presentationmentioning
confidence: 90%
See 1 more Smart Citation
“…Reports of NTM osteomyelitis in DM patients are rare, but given the recent increase in identification of NTM as pathogens, the possibility of NTM osteomyelitis in DM patients is worthy of more attention. DM can affect cytokine levels, chemotaxis and phagocytosis of monocytes and macrophages, and can cause an abnormal delayed-type hypersensitivity response [ 186 ]. These effects are particularly serious in elderly patients with DM, and may increase the risk of intracellular infections with pathogens such as NTM and tuberculosis [ 186 ].…”
Section: A Case Of Ntm Osteomyelitis Associated With Diabetes Mellitumentioning
confidence: 99%
“…DM can affect cytokine levels, chemotaxis and phagocytosis of monocytes and macrophages, and can cause an abnormal delayed-type hypersensitivity response [ 186 ]. These effects are particularly serious in elderly patients with DM, and may increase the risk of intracellular infections with pathogens such as NTM and tuberculosis [ 186 ]. Osteomyelitis is a complication of DM, and is associated with increased mortality, as well as increased costs [ 187 ].…”
Section: A Case Of Ntm Osteomyelitis Associated With Diabetes Mellitumentioning
confidence: 99%